Influencia del taller "LEARNING BY ACTING" en la producción oral del idioma inglés de los estudiantes del 5° "a" del nivel primario de la l.E.P. San Lucas, Tarapoto - 2014 - Slater Ipushima, Josue (2015)
The present work of research carne out of the need for improving the oral production of the English language of the students of the 5° grade "A" of the primary level of the P.E.I San Lucas-Tarapoto 2014, since we observed deficiency upon the students to express orally in the English Language. The research had as a main objective to develop the oral production of the English Language by means of the methodological proposition "LEARNING BY ACTING" which used as a main strategy the THEATER as a didactic resource, which took place in eight workshops. Our research was based upon a constructivist approach, which manifested itself the existence and enduring of the active processes in the construction of new insights. The workshop "LEARNING BY ACTING" was specifically designed with the purpose of improving the oral production of the students of the 5° grade "A" of the primary level of the P.E.I San Lucas- Tarapoto 2014, this workshop had three stages which were: WARMING-UP, INTERACTING ANO PERFORMANCE and therefore the THEATER was used achieving that the student would keep their attention all the time. At the end of the 8 workshops, significance was observed regarding the improvement of the oral production of the students, since they showed to be able to express their ideas and emotions according to the different topics given; then the computing tab of data was done, the description and the respective analysis. We compared the obtained data before and after of the application and the result of grades of the 8 workshops. We evaluated four components in the oral production: fluency, coherence, cohesion and intonation. The results showed that the methodological proposition "LEARNING BY ACTING" affected meaningfully upon the development of the oral production. This achievement was due to the methodology designed under coordination towards the teaching-learning of the second language.